2014
DOI: 10.1080/07399332.2014.942902
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Consistent Condom Use Among Chinese Female Sex Workers: An Application of the Protection Motivation Theory

Abstract: We utilized the Protection Motivation Theory (PMT) to assess predictors of intention and behavior of consistent condom use among Chinese female sex workers (FSWs). A self-administered questionnaire was used in a cross-sectional survey among 700 FSWs in Guangxi, China. Multivariate logistic regression analysis indicated that extrinsic and intrinsic rewards, self-efficacy and response costs predicted consistent condom use intention and behavior among FSWs. STI/HIV prevention programs need to reduce FSWs’ percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…The research result showed a relation between self-efficacy and risky sexual behavior. The result was consistent with the study of Zhang et al (2015), who found that the high self-efficacy of female CSWs has a significant relation with the consistency of condom usage with their regular partners. A study by Markosyan et al (2007) also revealed that the high frequency of condom usage by regular partners and irregular partners is related to the high self-efficacy of female CSWs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The research result showed a relation between self-efficacy and risky sexual behavior. The result was consistent with the study of Zhang et al (2015), who found that the high self-efficacy of female CSWs has a significant relation with the consistency of condom usage with their regular partners. A study by Markosyan et al (2007) also revealed that the high frequency of condom usage by regular partners and irregular partners is related to the high self-efficacy of female CSWs.…”
Section: Discussionsupporting
confidence: 92%
“…The variable with the greatest effect on risky sexual behavior was self-efficacy. The research result was consistent with that of Zhang et al (2015), who found that in a multivariate analysis, self-efficacy is a critical predictor of consistency of condom usage with regular and irregular partners. Control over infection due to risky sexual behavior requires self-efficacy for honest communication with partners (Mcdonough, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PMT is a social cognitive model that prioritizes relevant cognitions in predicting protective behaviors. This theory has been used in investigating condom use for HIV prevention, 22,23 protective behavior for schistosomiasis prevention, 24 and tobacco smoking. 21 A meta-analytic review suggests that PMT may also be applicable to investigate screening motivation and subsequent uptake by considering social influence and previous health care experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PMT may be a good predictor of protective behaviors, like smoking/tobacco use [16,17], cancer preventive behaviors [18,19], cancer screening [20,21], and sexual behaviors [22,23] PA behavior [24]. Theory-based studies on PA behavior are important for designing effective intervention programs.…”
Section: Introductionmentioning
confidence: 99%